Investigating the Effects of Minimum Wage and Non-Compliance on Formal Employment: Evidence in Java Island - Fadhilah, Mutiara Gita; Damayanti, Arie (Eko-Regional: Jurnal Pembangunan Ekonomi Wilayah, 2024)
There is an ongoing debate in the field of minimum wage literature, with different theories predicting varying impacts on employment. According to neoclassical theory, when the minimum wage increases and becomes binding, employment decreases. However, the monopsony labor market theory predicts that minimum wage can increase employment. Empirical examination in Indonesia has yielded mixed results, depending on the data and empirical model specification. Our study used panel data of regencies/cities in Java Island between 2017 to 2021 period and the fixed effect estimation method. We found that the minimum wage can increase employment in the formal sector, but the effect diminishes as non-compliance increases. This suggests that the benefit of a minimum wage in protecting workers depends on enforcement and that weak enforcement and setting a minimum wage too high may cause more non-compliance, which could harm formal employment.